Educational capabilities and aspirations of informal market women: the case of the "Stop 'N Shop" informal open market in Windhoek, Namibia - Ngunaihe, Paskaline Ngayozikue (University of the Free State, 2023)
Accounting for more than 60% of the world’s population, the informal economy is known to be where they earn their income and livelihoods (International Labour Organization (ILO), 2018). In Namibia and many parts of the world, the prevalence of the informal sector has been apparent enough to make it a worldwide phenomenon, regardless of the socio-economic development of the various countries. However, the majority has been recorded higher in developing countries. Employment in the informal sector is globally higher for men at 63% and 58% for women, but women are found to be involved in the most vulnerable types of work or from home-based spaces (ILO, forthcoming). In addition to that, women are said to represent about 70% of the global poor (Golla, Malhotra, Nanda, & Mehra, 2011). Moreover, it is evident across various literature that the empowerment of women market workers in the informal economy is a factor that influences growth in choices, improved livelihoods, and the advancement of gender equality. In relation to the attainment of the latter, education is an asset so crucial for women that it provides them with a range of positive options; this includes reduced, early childbearing and marriage, they are more involved in decision-making, more aware of their rights and they have greater access to better employment opportunities (United Nations Women, 2015). Per the Namibia Informal Economy Case Study Report (2016/17), nearly 70% of the own-account workers engaged in the informal sector are, most importantly, female (Ministry of Labour, Industrial Relations, and Employment Creation (MLIREC) and Social Security Commission (SSC), 2018). Thus, this study aims to explore and comprehensively investigate the impact of education, employment, and capacity-building initiatives within the informal sector, especially on women 18 – 44 years working in the informal markets through international literature, while examining the dynamics of gender inequality and education in the informal sector regarding their impact on access to opportunities (capabilities) and basic resources for this collective of women. Additionally, it explores educational pathways and aspirations of women in the informal sector operating from the Stop ‘N’ Shop informal market in Okuranyangava, Windhoek, in Namibia. The study utilized a Qualitative Hermeneutic Approach, which is inherently phenomenological in nature, used as a model to uncover from human experiences meaning and essence, deductive from the conceptual framework guided and framed through Sen’s (1999) capability approach. In line with the above methodology, this study will use appropriate data collection methods and semi-structured in-depth interviews with the market women 18 – 44 years to gain further insight into this phenomenon. The results found that Market women face several challenges that affect their gender equality to the extent that they are limited to a fast number of multi-faceted responsibilities as they navigate care for their children, extended families, husbands, siblings, and parents. The latter is in addition to women in the informal market experiencing uneven access to resources and income, which are dynamics that further confine them in accessing and attaining their basic resources, educational, aspirational needs, and capabilities due to these many causes. However, the most common is the lack of education and the financial resources to attain education to set up a sustainable livelihood for themselves and their families. It is imperative to note that the findings emphasize that the sacrifices of exploring market opportunities can be tremendous, such as migration from one area to another, especially from a rural area to a more urban and developed area, in this case to Windhoek, the capital City of Namibia in search of growing opportunities for their livelihood improvement, even facing circumstances of lack of safety, infrastructure, and service as they embark an opportunity-seeking journey that has educational aspirations at heart. Results and findings with the Non-Governmental Organizations and local government representatives that work with the “Stop ‘N Shop” market to get a better understanding of the opportunities available for market women, they reveal that the different organizations provide various initiatives for women in the informal economy. However, these initiatives seem to come at a fee. Thus it is safe to say that informal employment earnings for women market workers context limits them to divert their income to cover their education and educational desire increasing their chances of remaining in the cycle of poverty. The finding also establish that supporting women in informal markets with resources and training is an essential long-lasting relationship builder, especially of small livelihood sustaining and improving women’s businesses in the market. In addition, the educational institutions find it imperative that education and research goals can be explored through inclusive means such as mature entry and recognition of prior learning (RPL) in higher education and technical and vocational education and training (TVET), to establish the needed gender equality in education and community engagement to ensure the contribution of education is in line with the women’s educational aspirations and challenges they face as a market worker.
Dissertation(MDS (Development Studies))--University of the Free State, 2023
Keywords: Informal economy; Informal sector; "Stop 'n Shop" informal market; International Labour Organization (ILO); Qualitative Hermeneutic Approach